The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1007/bf00314080
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral amyloid angiopathy in the aged

Abstract: Cerebral amyloid angiopathy (CAA) was found in 57% of 123 autopsy brains removed from patients aged 59-101 years. The incidence of CAA increased with age. CAA was seen most frequently in the occipital cortex. Immunohistochemically, amyloid of CAA was positive for amyloid P component and negative for human AA protein and human prealbumin. The presence and severity of CAA were significantly correlated with the number of senile plaques and neurofibrillary tangles. The incidence of CAA in 17 patients with dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
117
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(140 citation statements)
references
References 32 publications
17
117
1
Order By: Relevance
“…The major component of NFTs is the microtubule-associated protein tau. It has been reported that ␤-amyloid, a peptide observed as an aggregated form in senile plaques of AD (5), cannot exhibit neurotoxicity and induce neurodegeneration without the existence of tau (6,7). As demonstrated in these studies, tau is considered to play a crucial role in inducing neurodegeneration.…”
mentioning
confidence: 88%
“…The major component of NFTs is the microtubule-associated protein tau. It has been reported that ␤-amyloid, a peptide observed as an aggregated form in senile plaques of AD (5), cannot exhibit neurotoxicity and induce neurodegeneration without the existence of tau (6,7). As demonstrated in these studies, tau is considered to play a crucial role in inducing neurodegeneration.…”
mentioning
confidence: 88%
“…22 In the past, the development of CAA had not been thought to correlate with the presence of common cerebrovascular risk factors, including hypertension, diabetes mellitus, hyperlipidemia, or the severity of atherosclerosis of the cerebral arteries. 23 Thereafter, the correlation between CAA, on the one hand, and cerebral arteriosclerosis and arteriolar sclerosis, on the other, has attracted attention. 6 Recently, the correlation in the severity of SVD and CAA was demonstrated by postmortem pathological investigation of elderly subjects.…”
Section: Relationship Between Caa-ich and Hypertensionmentioning
confidence: 99%
“…Brain autopsy studies demonstrated that CAA pathology occurs with a prevalence ranging from 2% at the age of 50 years old to 74% in subjects Ͼ90 years old. [1][2][3][4][5][6][7] Moreover, 92% to 98.5% of patients with Alzheimer disease also have CAA. 1,7 A distinct type of CAA with a genetic basis is called hereditary cerebral hemorrhage with amyloidosis-Dutch type (HCHWA-D).…”
mentioning
confidence: 99%